Lenvatinib Plus Pembrolizumab vs. Chemotherapy in Pretreated Patients With Advanced Endometrial Cancer: A Cost-Effectiveness Analysis - Feng, Mingyang; Chen, Yue; Yang, Yang; Li, Qiu (Frontiers in Public Health, 2022)
Background In the international, randomized, open-label, phase 3 study 309-KEYNOTE-775 trial, lenvatinib plus pembrolizumab (LP) showed improved progression-free survival (PFS) and overall survival (OS) compared with chemotherapy in pretreated patients with advanced endometrial cancer. This study aimed to investigate whether LP is cost-effective compared with chemotherapy. Materials and Methods The clinical data for this model was derived from the 309-KEYNOTE-775 trial. Costs and utilities were either derived from the standard fee database or extracted from previously published literature. A three-state Markov model was developed to simulate the disease process of patients with advanced endometrial cancer. One-way sensitivity analyses were conducted to investigate the impact of variables in the analysis model. Probabilistic sensitivity analysis was performed based on 10,000 Monte-Carlo simulations. A subgroup analysis was performed to test whether LP is cost-effective in patients with mismatch repair–proficient (pMMR) disease. Results Lenvatinib plus pembrolizumab provided an incremental 0.64 quality-adjusted life years (QALYs) with an incremental cost of $241,278.18, compared with chemotherapy, resulting in the incremental cost-effectiveness ratio (ICER) of $378,251.44/QALY, which exceeded the willingness to pay (WTP) threshold. While in the pMMR subgroup, the ICER increased to $413,256.68/QALY. The variance of the utility of PFS state, the cost of LP, and the utility of the progressive disease state were the most influential factors in the sensitivity analysis. Conclusion Under the current WTP threshold, LP is not cost-effective compared with chemotherapy in pretreated patients with advanced endometrial cancer.